White matter structure and myelin-related gene expression alterations with experience in adult rats. (April 2020) - Sampaio-Baptista, Cassandra; Vallès, Astrid; Khrapitchev, Alexandre A.; Akkermans, Guus; Winkler, Anderson M.; Foxley, Sean; Sibson, Nicola R.; Roberts, Mark; Miller, Karla; Diamond, Mathew E.; Martens, Gerard J.M.; De Weerd, Peter; et al.
Highlights: Somatosensory experience results in DTI changes in white matter (WM). Macroscale metrics of WM structure correlate with mRNA markers of cortical activity. MBP immunohistochemistry and mRNA expression indicate changes in myelin. Both molecular and cellular evidence are consistent with DTI findings. Myelination is one component of macroscale measures of WM plasticity. Abstract: White matter (WM) plasticity during adulthood is a recently described phenomenon by which experience can shape brain structure. It has been observed in humans using diffusion tensor imaging (DTI) and myelination has been suggested as a possible mechanism. Here, we set out to identify molecular and cellular changes associated with WM plasticity measured by DTI. We combined DTI, immunohistochemistry and mRNA expression analysis and examined the effects of somatosensory experience in adult rats. First, we observed experience-induced DTI differences in WM and in grey matter structure. C-Fos mRNA expression, a marker of cortical activity, in the barrel cortex correlated with the MRI WM metrics, indicating that molecular correlates of cortical activity relate to macroscale measures of WM structure. Analysis of myelin-related genes revealed higher myelin basic protein (MBP) mRNA expression. Higher MBP protein expression was also found via immunohistochemistry in WM. Finally, unbiased RNA sequencing analysis identified 134 differentially expressed genes encoding proteins involved in functions related to cell proliferation and differentiation, regulation of myelination and neuronal activity modulation. In conclusion, macroscale measures of WM plasticity are supported by both molecular and cellular evidence and confirm that myelination is one of the underlying mechanisms.